The McKissock's technique in reduction mammaplasty: A comparative study of outcomes and complications in 211 consecutive patients - Messana, Francesco; Grigatti, Martina; Budini, Valentina; Ricci, Federico; Brambullo, Tito; Bassetto, Franco; Vindigni, Vincenzo (Frontiers in Surgery, 2022)
Reduction mammaplasty is one of the most popular plastic surgery procedures requested by patients. The areola holder flap can be sculpted using a variety of methods that have evolved over time depending on the vascularity. Our institution has always employed the vertical bipedicle technique proposed by Mckissock, and we still favor it over other methods for larger breasts. In this study, we examined the case-study data from the Padua University Hospital's Unit of Plastic and Reconstructive Surgery from January 2009 to December 2021. The rate of complications among patients who received breast reduction using the McKissock technique and all other procedures carried out at our facility was compared. We identified 90 postoperative complication in total (affecting 42.65% of the patients) and categorized them using the Clavien Dindo classification. The groups were comparable in age, BMI, and follow-up time. Similar findings emerged from the study of the single groups' complication rate. The statistical analysis did not reveal any appreciable variation in total complications or scar quality between groups. Therefore, in order to guarantee NAC survival, a stable shape, and a full upper pole, we think it is preferable to secure more than one pedicle in cases of very large breasts. Based on the results of our experience, we also recommend the McKissock approach as the first option for patients with large and ptotic breasts, particularly those who have undergone bariatric surgery and need a full upper pole and a stable outcome.